Frontal-wave cyclogenesis in the North Atlantic -a climatological characterisation - Schemm, Sebastian; id_orcid:0 000-0002-1601-5683; Sprenger, Michael (Quarterly Journal of the Royal Meteorological Society, 2015)
ISSN:0035-9009 ISSN:1477-870X